Unusual cause of abdominal pain and jaundice in emergency: case report: Causa inusual de dolor abdominal e ictericia en emergencia: reporte de caso - Calcino-Cuela, Jessica Milagros (2024)
We analyzed a young man with a history of jaundice since childhood and cholelithiasis, who presented with abdominal pain, jaundice and splenomegaly. Initially, a diagnosis of dengue was considered, given the prevalence of this disease in the patient's geographic region. However, additional testing identified hereditary spherocytosis, a genetic hemolytic disorder. The importance of considering alternative diagnoses in the face of common symptoms in emergencies is emphasized. Initial dengue-oriented management was followed by targeted treatment for hereditary spherocytosis after the diagnosis was confirmed, resulting in significant improvement in the patient. This case emphasizes the need for thorough anamnesis and meticulous diagnostic evaluation to prevent diagnostic errors and inappropriate treatment, highlighting how inherited diseases can mimic infectious conditions in complex clinical scenarios.